Ultrasound in the Evaluation of Radial Neuropathies at the Elbow - Xiao, Ted G.; Cartwright, Michael S. (Frontiers in Neurology, 2019)
There are five sites at which radial nerve entrapment at the elbow has been commonly reported. These include the level of the fibrous bands within the extensor carpi radialis brevis, the thickened fascial tissue at the radiocapitellar joint, the Leash of Henry, the Arcade of Frohse, and the distal border of the supinator muscle. This review describes the anatomy of the radial nerve at the elbow and the surrounding structures, and then provides an overview of the literature supporting the use of ultrasound to assist in the evaluation of suspected radial neuropathy at the elbow. This review concludes with a suggested ultrasonographic approach for the systematic evaluation of suspected radial neuropathy at the elbow.